Design Research of Non-circular Gears on Continuously Variable Transmission - Sun Guoxing; Sun Chuanqiong; Li Bo; Zheng Fangyan (Jixie chuandong)
A new design approach of non- circular gear is proposed in order to solve the design problems of non- circular gear on continuously variable transmission. Using this approach,the transmission ratio function of non- circular gears composed by two functions in the entire cycle is smooth and continuous at the connection points,and then the cusps of the non- circular gear pitch curve are eliminated in order to ensure the smooth transmission. Finally,the example is given,the transmission ratio function of non- circular gears on continuously variable transmission is redefined and the non- circular gears of the smooth and continuous pitch curve is redesigned by using the approach. This approach can also be applied to the general design of non- circular gear.